Wave and scattering methods for numerical simulation - Bilbao, Stefan D. (J. Wiley, 2004)
Reliable prediction through modelling forms the basis of engineering design. Circuit-based methods for the numerical integration of partial differential equations offer electronic and electrical engineers a simple and verifiable technique for defining efficient and stable models.